Potential Therapeutic Action of Autophagy in Gastric Cancer Managements: Novel Treatment Strategies and Pharmacological Interventions - Rahman, Md. Ataur; Ahmed, Kazi Rejvee; Rahman, MD. Hasanur; Park, Moon Nyeo; Kim, Bonglee (Frontiers in Pharmacology, 2022)
Gastric cancer (GC), second most leading cause of cancer-associated mortality globally, is the cancer of gastrointestinal tract in which malignant cells form in lining of the stomach resulting indigestion, pain, and stomach discomfort. Autophagy is an intracellular system in which misfolded, aggregated, and damaged proteins as well as organelles are degraded by the lysosomal pathway, and avoiding abnormal accumulation of huge quantities of harmful cellular constituents. However, the exact molecular mechanism of autophagy-mediated GC management has not been clearly elucidated. Here, we emphasized the role of autophagy in the modulation and development of gastric cancer transformation in addition to underlying the molecular mechanisms of autophagy-mediated regulation of gastric cancer. Accumulating evidences have been revealed that targeting autophagy by small molecule activators or inhibitors are become one of the greatest auspicious approaches for gastric cancer managements. Particularly, it has been verified that phytochemicals play an important role in treatment as well as prevention of gastric cancer. However, use of combination therapies of autophagy modulators in order to overcome the drug resistance through gastric cancer treatment, which will provide the novel opportunities to develop promising gastric cancer therapeutic approaches. Additionally, it is urgently needed for the investigations of the pathophysiological mechanism of GC with potential challenges as well as limitations of the modulation of autophagy-mediated therapeutic strategies. Therefore, in this review, we would like to deliver an existing standard molecular treatment strategy focusing on the relationship between chemotherapeutic drugs and autophagy which help to improve the current treatments of gastric cancer patients.